The acute effect of transitioning between strength and hypertrophy resistance training sessions in youth rugby league athletes - Doma, K.; Bartlett, L.; Sinclair, W.; Connor, J.; Leicht, A. (Journal of Science and Medicine in Sport, 2024)
Introduction: Youth rugby league athletes are increasingly engaging in rigorous resistance training to meet the demands of their sport. As part of periodisation, resistance training workload volume is typically altered in a wave-like progression (i.e. mesocycles). While exposure to an unfamiliar stimulus is desirable during periodisation, youth athletes may initially encounter elevated levels of exercise-induced muscle damage (EIMD), including delayed onset muscle soreness (DOMS), creatine kinase (CK), and loss of muscle function. Developing a greater comprehension of the acute responses to variations in resistance training workload volume could aid practitioners in managing symptoms of EIMD, ensuring training quality, and minimizing injury risks. Therefore, this study aimed to investigate the impact of transitioning between different mesocycles on indirect markers of muscle damage and muscle performance metrics in resistance-trained youth rugby league athletes.